Towards the end of life: An in-depth exploration of the role of Admiral Nursing in dementia care (Innovative practice). (February 2018) - Evans, Simon C; Harrison-Dening, Karen; Read, Kate
There are approximately 150 Admiral Nurses in the UK who work alongside other health and social care professionals to support people with dementia and their family carers. However, the stigma of the disease and the lack of recognition that dementia is a life limiting illness have led to neglect in addressing the end of life challenges. The small in-depth study reported here aimed to add to an extremely limited formal evidence base for the effectiveness of this approach and to develop a greater understanding of the range of knowledge and skills required of them in ensuring they are better able to support families in the later stages of the illness. Findings focus on the experiences of family carers, the impact of performing the Admiral Nurse role and the use of qualitative measures in this setting.